The role of argumentative practices within advice-seeking activity types. The case of the medical consultation - Bigi, Sarah (Rivista Italiana di Filosofia del Linguaggio)
Advice seeking and advice giving have been studied both as speech acts and as complex discursive activities in various dialogical contexts. One particularly interesting aspect involved in the acts of seeking and giving advice is the negotiation of the epistemic status of the parties involved and it is interesting to observe the role played by argumentative practices in the achievement of this goal. In particular, it is argued that argumentation sequences may appear in advice-giving activities with two main functions: as the pivotal elements of pragmatic argumentation (i.e., providing reasons for supporting or refusing a certain proposal for action); and as dialogic tools for the alignment of assessment criteria for decision making. As a consequence, argumentation sequences emerge as decisive moments in the learning process leading to radical conceptual change. In this paper, the functions of argumentative practices within advice-giving activities are exemplified in relation to the goals of medical encounters, analyzed as instances of advice-seeking activity types. The analysis is based on excerpts from real-life interactions in different medical settings.